2010
DOI: 10.1186/1742-4690-7-50
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-1 in rural Guinea-Bissau: prevalence, incidence and a continued association with HIV between 1990 and 2007

Abstract: BackgroundHTLV-1 is endemic in Guinea-Bissau, and the highest prevalence in the adult population (5.2%) was observed in a rural area, Caió, in 1990. HIV-1 and HIV-2 are both prevalent in this area as well. Cross-sectional associations have been reported for HTLV-1 with HIV infection, but the trends in prevalence of HTLV-1 and HIV associations are largely unknown, especially in Sub Saharan Africa. In the current study, data from three cross-sectional community surveys performed in 1990, 1997 and 2007, were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 52 publications
2
29
0
Order By: Relevance
“…Most of the HIV burden is located in Sub-Saharan Africa though it is home to only 12% of the global population (Lozano, Naghavi et al 2012). Furthermore the prevalence of HIV is higher among women compared to men (van Tienen, van der Loeff et al 2010). Annually about 400,000 children are being infected with HIV of whom 90% (300,000) are due to mother to child transmission of HIV (MTCT) (Tudor Car, van-Velthoven et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the HIV burden is located in Sub-Saharan Africa though it is home to only 12% of the global population (Lozano, Naghavi et al 2012). Furthermore the prevalence of HIV is higher among women compared to men (van Tienen, van der Loeff et al 2010). Annually about 400,000 children are being infected with HIV of whom 90% (300,000) are due to mother to child transmission of HIV (MTCT) (Tudor Car, van-Velthoven et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The upper age limit of children was chosen assuming that sexual activity has mostly not started by this age in this population. 10 The area of living was defined as central or peripheral as previous studies showed different prevalences of HIV and HTLV-1 in the central and peripheral areas of Caió . 10 Medical care was provided by the project's physician when needed.…”
Section: Methodsmentioning
confidence: 99%
“…10 The area of living was defined as central or peripheral as previous studies showed different prevalences of HIV and HTLV-1 in the central and peripheral areas of Caió . 10 Medical care was provided by the project's physician when needed. At the time of the study no anti-retroviral therapy was available in Guinea-Bissau.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations